Psoriasis is Associated with a High Comedication Burden: A Population Based Register Study - Albert Duvetorp; Ulrich Mrowietz; Mats Nilsson; Oliver Seifert (Adis, Springer Healthcare, 2020)
Abstract Introduction A large body of evidence supports the association between psoriasis and concomitant diseases. However, the study of comedication for these diseases in patients with psoriasis is limited. The current study aimed to investigate the prescription and drug dispensation for comorbidity associated with psoriasis. Methods We conducted a retrospective case-control study from 9 April 2008 until 1 January 2016 using an electronic medical records database covering the entire population of the County of Jönköping and the Swedish Prescribed Drug Register. ICD-10 and Anatomical Therapeutic Chemical codes were used to identify patients with psoriasis and dispensed pharmaceutical prescriptions. Individuals without psoriasis were selected as controls. Patients receiving systemic treatment for psoriasis were considered as having moderate-severe psoriasis. Odds ratios for being dispensed pharmaceutical prescriptions and differences in mean number of dispensed prescriptions were explored. Results A total of 4587 patients with psoriasis were identified in the medical records, and 268,949 individuals served as controls. Patients with psoriasis had a significantly higher number of different drug dispensations compared to controls. Only 1.3% of all patients with psoriasis were without any prescription (excluding medication for psoriasis) during the study period while the number in the general population was 9.3%. Sex- and age-adjusted odds ratios for dispensation of drug groups related to comorbid disease were significantly higher among patients with psoriasis including drug groups such as anxiolytics and sedatives as well as drugs targeting COPD, migraine and erectile dysfunction. The most frequently dispensed comedications were oral antibiotics and analgesics including an increased risk for dispensation of opioids. Sex predisposed dispensation frequency for a variety of drug groups. Drugs targeting obesity, osteoporosis, psychiatric disease and anti-mycotics/-fungals were more frequent among women. Conclusion Patients with psoriasis have significantly increased numbers of different dispensed prescriptions than those without psoriasis. This underlines previous findings on increased comorbidity and health care costs for patients with psoriasis.